Intravenous Iron for Treatment of Anemia in the 3 Perisurgical Phases: A Review and Analysis of the Current Literature. (April 2018) - Peters, Frank; Ellermann, Ines; Steinbicker, Andrea U.
Abstract : Anemia is a common comorbidity throughout the entire hospital stay. Treatment options include intravenous (IV) iron, oral iron, erythropoietin, and red blood cell (RBC) transfusions. IV iron has gained in popularity with the implementation of patient blood management programs. A variety of studies have been performed to investigate the use of IV iron in preoperative, perioperative, and postoperative settings. An objective review on these studies has yet to be performed. The current narrative review provides an overview of trials investigating IV iron use in the preoperative, perioperative, and postoperative settings. We performed a literature research of English articles published between 1964 and March 2017 in Pubmed including Medline and The Cochrane Library. Only studies with a control group were included. The final review includes 20 randomized controlled trials (RCTs), 7 observational trials, and 5 retrospective studies. Measured outcomes included hemoglobin (Hb) levels, reticulocyte counts, and/or RBC concentrates. Meta-analyses of RCTs using IV iron administration before surgery led to an increase in Hb levels, a reduction of RBC use, and an improvement in patient outcome. Only a few studies investigated the use of IV iron in the perioperative setting. These studies recommended the use of perioperative IV iron in cases of severe anemia in orthopedic surgery but not in all types of surgery. Published RCTs in the postoperative setting have shown positive effects of IV iron on Hb levels, length of hospital stay, and transfusion requirements. Some studies demonstrated an increase of Hb of 0.5–1 g/dL over 4 weeks postoperatively, but the clinical relevance and effect of this increase on an improvement of patient's long-term outcomes are uncertain. To summarize, the evidence to use IV iron is strongest in the preoperative setting, while it remains an individual treatment decision to administer IV iron perioperatively or postoperatively.